2013
DOI: 10.1093/infdis/jit643
|View full text |Cite
|
Sign up to set email alerts
|

HIV "Elite Controllers" Are Characterized by a High Frequency of Memory CD8+CD73+ T Cells Involved in the Antigen-Specific CD8+ T-cell Response

Abstract: Human immunodeficiency virus type 1 (HIV-1) infection is characterized by chronic immune activation and suppressed T-lymphocyte functions. Here we report that CD73, both a coactivator molecule of T cells and an immunosuppressive ecto-enzyme through adenosine production, is only weakly expressed by CD8+ T cells of HIV-infected patients and only partially restored after successful antiviral treatment. CD73 expression on CD8+ T cells correlates inversely with cell activation both ex vivo and in vitro. However, CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…A prior publication showed an inverse correlation between CD73 expression and CD8 T cell activation [13]. We too observed a negative correlation for the combined EC group which was most likely driven by the EC hi group (figure 4B).…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…A prior publication showed an inverse correlation between CD73 expression and CD8 T cell activation [13]. We too observed a negative correlation for the combined EC group which was most likely driven by the EC hi group (figure 4B).…”
Section: Resultssupporting
confidence: 64%
“…Additionally, in this group, maintenance of CD28 expression, a co-stimulatory molecule which is commonly reduced during chronic HIV infection was retained. A recent study found that CD73, a coactivator of T cells [13] was elevated in all EC. However our data shows that this is only observed for the EC hi group and therefore cumulatively indicates that the EC hi group manifests a phenotype of functionally responsive T cells that is similar to healthy seronegative adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a distinct role for CD39 has been shown in the suppression of T effector cell functions [18]. Parallel to the expansion of CD39 + regulatory T cells, general down-regulation of CD73 on all T cell subsets was observed in HIV infection, which correlated with immune activation and functional defects of these cells [21,23,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…CTLs from HCs mediate more efficient HIV inhibition in vitro (10)(11)(12), polyfunctional secretion of cytokines such as IL-2 and IFN-γ (1,10,11), greater antigeninduced proliferation (10,13), less T cell activation (4), and evasion of regulatory T cell suppression (14). CTLs from HCs may also be phenotypically more inclined to protect from HIV infection for long durations (9,15) and sustain effector functions without T cell exhaustion (16). Several HLA-I alleles, including B*2705 and B*5701, are enriched in HCs (17,18), underscoring the role of CTLs in suppressing HIV infection.…”
mentioning
confidence: 99%